2014
DOI: 10.3164/jcbn.14-10
|View full text |Cite
|
Sign up to set email alerts
|

The role of lipid peroxidation in neurological disorders

Abstract: There has been much evidence demonstrating the involvement of oxidative stress in the pathology of neurological disorders. Moreover, the vulnerability of the central nervous system to reactive oxygen species mediated injury is well established since neurons consume large amounts of oxygen, the brain has many areas containing high iron content, and neuronal mitochondria generate large amounts of hydrogen peroxide. Furthermore, neuronal membranes are rich in polyunsaturated fatty acids, which are particularly su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
148
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(158 citation statements)
references
References 90 publications
3
148
0
7
Order By: Relevance
“…These results are in concordance with previous reports of Braga et al [22]. In vitro lipid peroxidation studies are useful for the elucidation of possible mechanisms of peroxide formation in vivo [23], since the high concentration of polyunsaturated fatty acid membranes causes susceptibility to lipid peroxidative degradation [24]. In our assay it was found that arachidonic acid C20:46 and docosahexaenoic acid C22:63 from controls were more peroxidized than those from CO group.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in concordance with previous reports of Braga et al [22]. In vitro lipid peroxidation studies are useful for the elucidation of possible mechanisms of peroxide formation in vivo [23], since the high concentration of polyunsaturated fatty acid membranes causes susceptibility to lipid peroxidative degradation [24]. In our assay it was found that arachidonic acid C20:46 and docosahexaenoic acid C22:63 from controls were more peroxidized than those from CO group.…”
Section: Discussionsupporting
confidence: 82%
“…More specifically, a three-to four fold increase in intracellular ROS and elevated levels of lipid peroxidation markers have been detected in the brain of DS patients while vitamin E was able to decrease such markers (e.g. Shichiri, 2014). This effect was previously demonstrated by Lockrow et al (2009) showing that vitamin E supplementation decreased markers of OS in the brain and improved cognitive performance in mice.…”
Section: Discussionmentioning
confidence: 80%
“…Hydrogen peroxide is also formed in the reactions of some oxidases, for example monoamine oxidases [110]. A second class of cellular peroxides are organic hydroperoxides which include stereospecificallydefined prostaglandin and leukotrine hydroperoxides that are products of cyclooxygenases and lipooxygenases, respectively, as well as various hydroperoxides that are generated by unspecific oxidation of polyunsaturated fatty acids in membranes by radical-mediated lipid peroxidation [111].…”
Section: Gsh and Peroxide Detoxificationmentioning
confidence: 99%